Pengaruh Manajemen Laba Terhadap Biaya Modal Ekuitas (Studi pada Perusahaan Publik Sektor Manufaktur) - WIWIK UTAMI (The Indonesian Journal of Accounting Research, 2013)
The objectives of the research is to find out empirical evidence of the influence of earnings management on cost of equity capital.The population of this study was listed companies in the manufacturing sector at the Jakarta Stock Exchange, and the sample was determined based on the following criteria: (a) the annual report ended 31 December, and (b) book value of equity is positive. There were 92 companies meeting the criteria. Data analysis was carried out in terms of pool cross-section covering annual financial report during 2001–2002. Earnings management were measured by ratio of working capital accruals with sales, and cost of equity capital was estimated by Ohlson model. The research hypotheses were tested using multi regression with beta risk and size as control variables.The results of this research show that (1) earnings management had positive significant influence on cost of equity capital, and (2) sensitivity analysis of earnings management proxy show that ratio of working capital accruals with sales is the best proxy compared with Healy model, modified Jones model and Jones Model.